The Future of Unmanned Naval Systems: An Overview Of Efficiency Enhancements and Warfare Upgrades for Maritime Drones - Leman, Jere (My University, 2025)
The dramatic rise of tensions between various countries has been escalating since the larger-scale Russian invasion of Ukraine in 2022. At the same time, the robotics and autonomous systems fields are blooming with new inventions and technology for both civilian and military applications. Most of the existing autonomous systems are built on ground, air, or space platforms. However, in this thesis, maritime drones will be explored comprehensively to improve their efficiency and military aspects, considering that the field of marine robotics lags behind other robotics fields. The development of autonomous weapon systems is highly connected to the advancements in AI technology, which allows the fundamentals for such maritime drone systems. The two largest competitors, the United States of America and China, bolster billions annually to fund research and development of maritime drones. However, Ukraine and its innovative solutions offer more concrete use cases and developments that have come to the public’s attention during their asymmetric warfare against Russia. Ukraine has effectively defended its territorial waters using maritime drones alongside its much smaller navy compared to the Russian naval fleet. The reasoning for this thesis is to address three research questions: 1. What are the strategic and tactical implications of maritime drones in modern warfare? 2. How can maritime drones be optimized and equipped better? 3. What are the ethical and environmental considerations surrounding the deployment of maritime drones? And what kind of regulatory measures have been set for maritime drones? The thesis will present various maritime drones and their properties. Additionally, it will feature a maritime drone developed in collaboration with the Finnish National Defence University, the University of Turku, and the Turku University of Applied Sciences. The Meri-Turso is a maritime drone that improves efficiency and affordability through innovative design. The role of naval drones in modern warfare will be examined through an analysis of current conflicts.
Keywords: Maritime, Naval, USV, UUV, Autonomous Weapon Systems, Warfare